Game-based Assessment: The Development of Logical Reasoning Test - Firdaus, Wahyu Maulana; Sari, Novita; Januarsjaf, Aswin (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2024)
This study aims to test the validity of a game-based logical reasoning test tool called the Library Game. This tool consists of eight stimuli, each representing interrelated scenarios that follow a specific pattern to address problems. Data analysis results show that the eight stimuli in the Library Game are unidimensionally valid in measuring logical reasoning constructs (n=284, chi-square=30.742, df=21, p-value=0.078, RMSEA=0.040, CFI=0.996, TLI=0.995). Furthermore, the researchers calibrated the items using Item Response Theory (IRT) 1 PL (parameter logistic). The results show that all items fit the established model. The level of item difficulty ranges from easy to moderate (-0.962 to 0.122). Therefore, this test can provide optimal information when administered to a population with an average level of logical reasoning. In conclusion, instead of conventional methods (question-answer format), valid assessment tools can be developed through innovative games.